Different Isocaloric Meals and Adiposity Modify Energy Expenditure and Clinical and Metabolomic Biomarkers During Resting and Exercise States in a Randomized Crossover Acute Trial of Normal-Weight and Overweight/Obese Men. Issue 4 (10th January 2022) - Xiong, Quan; Sun, Liang; Luo, Yaogan; Yun, Huan; Shen, Xia; Yin, Huiyong; Chen, Xiafei; Lin, Xu
ABSTRACT: Background: Few studies have assessed the integrative effects of diet, BMI, and exercise on postprandial changes in energy and circulating metabolic profiles. Objectives: We aimed to assess the collective effects of 3 isocaloric meals high in carbohydrate (74.2% energy), fat (64.6% energy), or protein (39.5% energy) on energy expenditure and clinical and metabolomic biomarkers under resting and exercise conditions in normal-weight and overweight/obese men. Methods: This crossover controlled acute trial included 20 normal-weight (BMI, 18.5 to <24 kg/m 2 ) and 20 overweight/obese (BMI ≥24 kg/m 2 ) men aged 18–45 years. Each of 3 test meals was provided for 2 continuous days: a resting day without exercise, followed by an exercise day with a bicycling exercise of 50% maximal oxygen consumption (postprandial 90–120 minutes). Energy expenditure (exploratory outcome of primary interest) was measured using indirect calorimetry. Fasting and postprandial 2-hour serum clinical and metabolomic biomarkers (secondary interest) were measured. Mixed models were used to examine the effects of meal, time, and/or BMI category. Results: On the resting day, no significant between-meal differences were detected for energy expenditure. However, high-carbohydrate and high-fat meals induced the highest postprandial 2-hour increase in glucose (0.34 ± 0.15 mmol/L) and triglyceride (0.95 ± 0.09 mmol/L), respectively, while the high-protein meal reduced glucose (−0.48 ± 0.08 mmol/L) and total cholesterol (−0.01 ± 0.03 mmol/L; all P meal values < 0.001). On the exercise day, a high-carbohydrate meal significantly promoted the carbohydrate oxidation rate but suppressed the fat oxidation rate ( P meal < 0.05), while its postprandial glucose response was attenuated by bicycling (−0.31 ± 0.03 mmol/L; P exercise < 0.001). We identified 69 metabolites as key features in discriminating between the 3 meals, and overweight/obese men had more varieties of metabolites than normal-weight men. Conclusions: Three isocaloric meals induced unique postprandial changes in clinical and metabolomic biomarkers, while exercise prevented the hyperglycemia induced by a high-carbohydrate meal. Overweight/obese men were more responsive to the meal challenges than normal-weight men. This trial was registered at clinicaltrials.gov as NCT03231618.